Choice of language in the teaching of science in English in the Malaysian classroom - 456862 Tan, Hooi Koon (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Sains serta Pendidikan (Pengajaran Bahasa Inggeris sebagai Bahasa Kedua)) - Universiti Teknologi Malaysia, 2006